PERSEPSI SISWA SMK TENTANG KETERAMPILAN MENGAJAR MAHASISWA PKM PROGRAM KEAHLIAN TEKNIK BANGUNAN - Regita Julianti; Tuti Iriani; R Eka Murtinugraha (LPPM Universitas Negeri Jakarta, 2015)
This research aimed to understand students’ perception about PKM students teaching skills majoring in building technique. The research took places in SMKN 1 Jakarta, SMKN 4 Jakarta, SMKN 26 Jakarta, SMKN 35 Jakarta, SMKN 58 Jakarta, and SMKN 1 Cibinong in between April-May 2015.The method used in this research is the Survey method. The subjects of this research were the student from the 10th grade that are taught theoretically by the teachers from the PKM program from Civil Engineering, State University Of Jakarta 102 semester, while the population consists of the student from SMKN 1 Jakarta, SMKN 4 Jakarta, SMKN 26 Jakarta, SMKN 35 Jakarta, SMKN 58 Jakarta, and SMKN 1 Cibinong Program Building Engineering expertise as much as 532 students in those vocational schools, and 221 samplers were taken by purposive sampling method. The instruments used in this research to collect the data about the students perception, are questionnaire about students perception on PKM students teaching skills majoring in building technique. The data processing is valid and reliable, with very high reliability number of r11= 0,956, with 32 numbers of questions.The result shows that the PKM students are skilled already in questioning (85%), giving variation (68%), explaining (67%), class management (72%), starting and closing the lesson (69%), guiding small groups (67%), and teaching small groups and individual (70%). Yet in giving reinforcement, it is still considered as low (49%).